Max Weber and Modernity: modernization, rationalization, legitimation - Roman Borysov (Український соціологічний журнал, 2020)
The paper reveals the features of sociological theorizing offered by classical sociology, including M. Weber's concept. The thematic directions that became central to the German scholar's sociology are identified: modernization, rationalization, legitimization, etc.; their genesis is analyzed from the point of view of the philosophical (Baden School of Neo-Kantianism) and sociological (G. Simmel's concept of cultural forms) studios. It is emphasized that rationalization, which was first considered by M. Weber, becomes a cross-cutting theme in sociology up to the end of the twentieth century. Further development of the concept of rationalization takes place within the communicative turn, associated with the name of J. Habermas. The concept of constructing the social, taking into account the meaning that the author puts into his actions, becomes the first attempt of theoretical synthesis in the process of overcoming the methodological crisis in sociological science. M. Weber's sociology offers a departure from the "container approach" in the analysis of society, which was later realized within the world-systemic (A. G. Frank, I. Wallerstein, J. Arrighi, etc.) and synthetic (M. Archer, P. Bourdieu, E. Giddens, P. Sztompka, etc.) concepts. The problematic of a bureaucratization, formulated by M. Weber in the early twentieth century to describe the processes of formation of the modern state, acquires new relevance today in connection with the expansion of the "bureaucratic spirit" to commercial enterprises, built according to the network logic. The tendencies of (self-)management on the part of employees, which are accelerating due to the transition to the remote form of work. The author shows how processes of legitimation, which are necessary for the perception of changes in professional activity, simultaneously contribute to the fragmentation and disintegration of local social spaces.